Beyond the DSGE straitjacket - Hashem Pesaran; Ron P. Smith (Institute for the Study of Labor (IZA), 2011)
Academic macroeconomics and the research department of central banks have come to be dominated by Dynamic, Stochastic, General Equilibrium (DSGE) models based on micro-foundations of optimising representative agents with rational expectations. We argue that the dominance of this particular sort of DSGE and the resistance of some in the profession to alternatives has become a straitjacket that restricts empirical and theoretical experimentation and inhibits innovation and that the profession should embrace a more flexible approach to macroeconometric modelling. We describe one possible approach.
urn:nbn:de:101:1-201104283168
Keywords: C1; E1; 330; macroeconometric models; DSGE; VARs; long run theory; Ökonometrisches Makromodell; Dynamisches Gleichgewicht; Kritik; Theorie